Aktivitas Antiparkinson Ekstrak Gambir (Uncaria Gambir Roxb.) Pada Tikus Putih (Rattus Norvegicus) Galur Sprague Dawley yang Diinduksi Haloperidol - Lutfi Nofitasari; Jason Merari Peranginangin; Sri Rejeki Handayani (Jurnal Farmasi Indonesia, 2017)
Parkinson disease is a disease that occurs due to damage to dopaminergic nerve cells in the brain which resulted in decreased dopamine production. Gambir is a dry extract made from the leaves of Uncaria gambier Roxb plant. Gambir contains flavonoids in the form of catechins not less than 90%, alkaloids and terpenoids. This study aims to determine the activity of gambir extract that can reduce the symptoms of Parkinson's in the male rats Sprague dawley induced haloperidol.Test animals of 35 rats divided into 7 groups. Group I (healthy control) was given aquadest orally, group II (negative control) was given a 0.5% CMC-Na solution, group III (positive control I) was given levodopa 27 mg / kgbb po, group IV (positive control II ) Were given vitamin E 180 IU / kgbb po Groups V, VI, and VII were given a dose of 70 consecutive gambir extracts; 140; 280 mg / kgbb. The whole group induced haloperidol 2 mg / kgbb i.p at the 45th minute after treatment except in the healthy group. Then the group was tested with a catalepsy bar test, recorded time latency expressed in scores and rota test rods, recorded time of latency in seconds on days 0, 4, 7, 11, and 14.The result of the research using catalepsy bar test method showed a decrease of catalepsy in gambir extract dose 70; 140; 280 mg / kgbb has a successive activity of 22.53; 52.50; 57.12%. While the results with rota rod test method showed% increase in time latency extract gambir respectively of 27.69; 35.75; 39.61%.